LINGUOCULTURAL ASPECTS OF ADDRESS FORMS IN ENGLISH AND GERMAN - Xodjiyeva Nilufar Gʻofur qizi,; Sobirova Zebo Bahromovna, (TADQIQOTLAR, 2026)
Abstract:  The  present  article  examines  the  linguocultural  aspects  of  address forms  in  English  and  German  languages.  Address  forms  play  an  important  role  in communication because they reflect social relations, cultural norms, and politeness strategies  within  a  speech  community.  The  study  focuses  on  how  cultural  values influence  the  choice  of  address  forms  in  both  languages.  The  research  analyzes linguistic  units  such  as  titles,  pronouns,  and  honorific  expressions  that  are  used  to address people in different communicative situations. The findings show that although both languages belong to the Germanic language family, their systems of address forms demonstrate  both  similarities  and  differences  due  to  historical  development  and cultural traditions.